1998
DOI: 10.1007/s004490050508
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration of blood proteins by experimental polyamide membranes

Abstract: The most important proteins in animal blood as haemoglobin, bovine serum albumin and c-globuline were ®ltered in experimental UF membranes. The membranes were prepared in our laboratory by the traditional phase inversion process using as polymer a new polyamide. These membranes were characterized by measuring their initial water¯uxes, and after that the protein solutions were ultra®ltered. The¯ux decline and membrane fouling were studied in order to obtain the best operating conditions for a future pilot plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…All the buffer solutions were adjusted to desired pH values by mixing different amounts of potassium dihydrogen phosphate (KH2PO4) and disodium hydrogen phosphate (Na2HPO4) (both from Fluka) in Milli-Q water and using these solutions within 3 days of preparation. Phosphate buffer saline solutions maintaining different external pH with low ionic strength (I ¼ 0.01 M) were used in the experiments 38 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the buffer solutions were adjusted to desired pH values by mixing different amounts of potassium dihydrogen phosphate (KH2PO4) and disodium hydrogen phosphate (Na2HPO4) (both from Fluka) in Milli-Q water and using these solutions within 3 days of preparation. Phosphate buffer saline solutions maintaining different external pH with low ionic strength (I ¼ 0.01 M) were used in the experiments 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Size-based separation of proteins can be carried out by ultrafiltration membrane systems when the proteins are significantly different in size 38,39 . However, separation of similarly sized proteins with the commercially available membranes is not possible 40 .…”
Section: Preparation and Characterization Of Nanoporous Particlesmentioning
confidence: 99%
“…Separation of proteins can be effectively carried out with membrane separation processes. In general, proteins are easily separated with porous membranes if the proteins have significantly different molecular sizes. However, membrane separation of similar size proteins, such as hemoglobin and albumin, is more difficult, and these separations have received renewed interest.…”
Section: Introductionmentioning
confidence: 99%
“…Existing processes for bioseparations using conventional resin-based chromatography are time-consuming and expensive. , Newly developed membrane separation processes offer substantial economic, environmental (less energy consumption), and safety benefits. , Micro/nanofabricated membranes with various pore sizes, lengths, morphologies, and densities have been synthesized from diverse inorganic, organic, and composite materials. Studies of nanostructured membranes have demonstrated their great potential in biomolecule separation applications. Size-based separation of proteins can be carried out by ultrafiltration membrane systems when the proteins have significantly different molecular sizes. However, separation of similar-sized proteins with current commercially available membranes is not possible . Recently, Striemer et al .…”
mentioning
confidence: 99%